Five‐year survival with nivolumab in previously untreated Japanese patients with advanced or recurrent malignant melanoma. Issue 5 (14th March 2021) - Uhara, Hisashi; Kiyohara, Yoshio; Uehara, Jiro; Fujisawa, Yasuhiro; Takenouchi, Tatsuya; Otsuka, Masaki; Uchi, Hiroshi; Fukushima, Satoshi; Minami, Hironobu; Hatsumichi, Masahiro; Yamazaki, Naoya
Abstract: We report the 5‐year follow‐up results from a single‐arm, open‐label, multicenter phase II study (ONO‐4538‐08) conducted in Japan. Twenty‐four patients with treatment‐naïve, recurrent, or unresectable stage III/IV malignant melanoma received 3 mg/kg nivolumab every 2 weeks until progressive disease or unacceptable toxicity occurred. The 5‐year overall survival (OS) rate was 26.1%. Five years after the start of nivolumab treatment, there were six survivors. The 5‐year OS rate was 66.7% for patients with a superficial spreading type, 14.3% for acral lentiginous type, and 16.7% for mucosal type. The 5‐year progression‐free survival rate was 17.2%. No new cases of partial response or complete response were observed after 3 years, and overall response and disease control rates were similar to those reported at 3 years. The treatment‐related adverse events reported between the 3‐ and 5‐year follow‐up periods were anemia (grade 2), white blood cell count decrease (grade 2), and psoriasiform dermatitis (grade 2) in one patient each. No new grade 3 or higher treatment‐related adverse events occurred in this period. In conclusion, first‐line treatment with nivolumab in Japanese patients with unresectable or metastatic melanoma resulted in confirmed long‐term survival. No new safety signals were reported in the studied population.